Monitoring stick speed and ball control in field hockey drills using a stick-mounted inertial accelerometer - Thiel, D. V.; Tremayne, M.; James, D. A. (Procedia Engineering, 2012)
Field hockey is a stick based sport where stick speed and ball control are primary skills. A stick mounted accelerometer was used to record hit events and the timing between them. The objective was to assess skill level using inter-hit timing in single-player drills. Eleven novice and nine state ranked male players performed three drills on artificial turf using both forehand and reverse stick hits at maximum stick speed. A 44 g stick-mounted 3-axis accelerometer was used to distinguish between forehand and reverse stick ball strikes and determine the time between ball strikes. Timing data and linear regression analysis was used compare the drills. The Chapman ball control test which requires no directional control recorded a shorter inter-hit time compared to other drills where the ball direction was prescribed. Reverse-stick drills take the longest time for effective ball disposal. Reverse stick drills requiring control of the ball direction are not commonly part of skills training and the speed of ball delivery is much lower when compared to similar forehand drills. The Modified Chapman ball control test results showed the highest correlation to hockey performance levels.